Dissolution behavior of solid stainless steel by its molten eutectic mixture with B4C under dynamic condition. (November 2019) - Sumita, Takehiro; Kobayashi, Yoshinao
Abstract: For decommissioning of severe accident reactors, it is necessary to conduct a detailed analysis on melting behavior of the core structural materials, such as the core support structure and the vessel walls, in severe accident condition. In particular, the eutectic melting between control rods (B4 C) and their cladding (stainless steel (SS)) have been concerned since the accident in Fukushima. This reaction causes SS-B4 C eutectic melt called molten metallic corium. It is considered that the formed molten metallic corium flowed down to the bottom of pressure vessel and dissolved the core structural materials, mainly made of SS, during the severe accident (SA). In order to predict the damage condition of the reactor after the accident, dissolution behavior of solid SS by molten metallic corium should be investigated. Previously, the authors reported that the dissolution of solid SS by molten metallic corium is mainly engendered by the grain detachment from solid SS (erosion) due to infiltration of molten metallic corium into the SS grain boundaries (corrosion), called corrosion-erosion. Moreover, regarding corrosion, it was reported that the infiltration of molten metallic corium into SS grain boundaries can be explained by the grain boundary diffusion of boron, and the grain boundary diffusion coefficient was estimated. Herein, the rotational immersion experiments of SS rods into molten metallic corium (SS-B4 C melt) were conducted in order to evaluate dissolution behavior of SS under dynamic condition, focusing on erosion. The findings from the experiments showed that the faster the rotational speed of SS rod specimen is and the larger the grain size is, the faster the dissolution rate becomes. Moreover, it can be considered that the dissolution rate of SS by molten metallic corium is faster compared to those in other systems, such as Fe-molten Cu system and steel-molten Al system. This reason would be explained as follows. Although activity coefficient of B is low in the Fe-B system and chemical reaction between materials is active, intermediate compound layer, which is the resistance of chemical interaction, does not form at the SS rod surface during dissolution as concentration of B in molten metallic corium is low. In the present study, influence of the temperature change, ranging from 1523 to 1623 K, on dissolution rate has been also investigated. It was found that the dissolution rate becomes faster with an increase in temperature. Apparent activation energy of dissolution is estimated to be about 240 kJ/mol, suggesting that the eutectic melting at the SS grain boundary is the rate-determining step. These findings suggest that the dissolution of core structural materials by molten metallic corium during the accident is strongly influenced by fluid flow and temperature of molten metallic corium. Highlights: Dissolution rate of stainless steel (SS) by molten metallic corium was measured. Dissolution rate increased linearly with increasing rotational speed of SS rod. The larger the grain size of SS is, the faster the dissolution rate is. Dissolution rate increased as the temperature increased from 1523 to 1623 K. Apparent activation energy of dissolution is estimated to be about 240 kJ/mol.